Paclitaxel modulates TGFbeta signaling in scleroderma skin grafts in immunodeficient mice. - Xialin Liu; Shoukang Zhu; Tao Wang; Laura Hummers; Fredrick M Wigley; Pascal J Goldschmidt-Clermont; Chunming Dong (PLoS Medicine, 2005)
BACKGROUND: Systemic sclerosis (SSc) is characterized by excessive fibrosis and obliterative vascular lesions. Abnormal TGFbeta activation is implicated in the pathogenesis of SSc. Aberrant TGFbeta/Smad signaling can be controlled by stabilization of microtubules with paclitaxel. METHODS AND FINDINGS: SSc and healthy human skin biopsies were incubated in the presence or absence of paclitaxel followed by transplantation into severe combined immunodeficient mice. TGFbeta signaling, fibrosis, and neovessel formation were evaluated by quantitative RT-PCR and immunohistochemical staining. Paclitaxel markedly suppressed Smad2 and Smad3 phosphorylation and collagen deposition in SSc grafts. As a result, the autonomous maintenance/reconstitution of the SSc phenotype was prevented. Remarkably, SSc grafts showed a 2-fold increase in neovessel formation relative to normal grafts, regardless of paclitaxel treatment. Angiogenesis in SSc grafts was associated with a substantial increase in mouse PECAM-1 expression, indicating the mouse origin of the neovascular cells. CONCLUSION: Low-dose paclitaxel can significantly suppress TGFbeta/Smad activity and lessen fibrosis in SCID mice. Transplantation of SSc skin into SCID mice elicits a strong angiogenesis-an effect not affected by paclitaxel. Although prolonged chemotherapy with paclitaxel at higher doses is associated with pro-fibrotic and anti-angiogenic changes, the findings described here indicate that low-dose paclitaxel may have therapeutic benefits for SSc via modulating TGFbeta signaling.